DUST PRODUCTION AND DEPOSITION IN ASIA AND THE NORTH PACIFIC OCEAN OVER THE PAST 12 MYR - Pettke T.; Halliday A.N.; Hall C.M.; Rea D.K. (My University, 2000)
The silicate fractions of recent pelagic sediments in the central north Pacific Ocean are dominated by eolian dust derived from central Asia. An 11 Myr sedimentary record at ODP Sites 885/886 at 44.7 degrees N, 168.3 degrees W allows the evaluation of how such dust and its sources have changed in response to late Cenozoic climate and tectonics. The extracted eolian fraction contains variable amounts (> 70%) of clay minerals with subordinate quartz and plagioclase. Uniform Nd isotopic compositions (epsilon(Nd) = -8.6 to -10.5) and Sm/Nd ratios (0.170-0.192) for most of the 11 Myr record demonstrate a well-mixed provenance in the basins north of the Tibetan Plateau and the Gobi Desert that was a source of dust long before the oldest preserved Asian loess formed. epsilon(Nd) values of up to -6.5 for samples <2.9 Ma indicate less than or equal to 35 wt% admixture of a young, Kamchatka-like volcanic are component. The coherence of Pb and Nd in the erosional cycle allows us to constrain the Pb isotopic composition of Asian loess devoid of anthropogenic contamination to Pb-206/Pb- 204 = 18.97 +/- 0.06. Pb-207/Pb-204 = 15.67 +/- 0.02. (208)pb/Pb-204 = 39.19 +/- 0.11. Sr-87/Sr-86 (0.711-0.721) and Rb/Sr ratios (0.39-1.1) vary with dust mineralogy and provide an age indication of similar to 250 Ma. Ar-40/Ar-39 ages of six dust samples are uniform around 200 Ma and match the K-Ar ages of modern dust deposited on Hawaii. These data reflect the weighted age average of illite formation. Changes from illite greater than or equal to smectite with significant kaolinite to illite- and chlorite-rich, kaolinite-free assemblages since the late Pliocene document changes in the intensity of chemical weathering in the source region. Such weathering evidently did not disturb the K-Ar systematics, and only induced scatter in the Rb-Sr data. We propose that when smectite forms at the expense of illite, K and Ar are quantitatively lost from what becomes smectite, but are quantitatively retained in adjacent illite layers. Ar-40/Ar-39 age data, therefore, are insensitive to smectite formation during chemical weathering but date the diagenetic growth of illite, the major K-bearing phase in the dust. Over the past 12 Myr, the dust flux to the north Pacific increased by more than an order of magnitude, documenting a substantial drying of central Asia. This climatic change, however, did not alter the ultimate source of the dust, and neoformational products of chemical weathering always remained subordinate to assemblages reworked by mechanical erosion in dust deposited in eastern Asia and the Pacific Ocean.
Keywords: Pliocene; Cenozoic; Кайнозой::Неоген::Плиоцен; Cenozoic; Cenozoic::Neogene::Pliocene; Кайнозой